Fish wastewater treatment with "PACP" filter and reuse of the treated water - Helal Uddin, A.B.M.; Saeed, Mohammad; Mohd Asri, Mohd Nawi (Lifescience Global, 2007)
Powdered activated carbon pellet (PACP) filter was found very effective for the removal of chemical oxygen demand (COD) and nutrient from the fish wastewater. It was found in the study that fish waste water generated from rearing tilapia fish in a glass aquarium for 48 hours had high organic and nutrient content. This high organic and nutrient containing wastewater while passed through the 30 cm PACP filter could remove 90% COD, 93% phosphate and 85% ammonia nitrogen after 10 L of fish wastewater loading. The optimum flow rate for the PACP filter was 100 ml/min. In a comparative study it was found that PACP filter had a better COD removal capacity compared to a same size granular activated carbon (GAC) filter. After 10 L loading of fish wastewater GAC filter showed only 50% removal where as it was 90% for PACP filter. PACP filter did not reach to the breakthrough level or exhausted after continuous loading of 35 L of fish wastewater. Filtered PACP filter wastewater was used for rearing tilapia fish and up to the fourth water changing with a 48 hour interval, the fish was in good condition and no death occurred.